The western Misconception on Islamic Polygamy: an assessment of Islamic Polygamy’s Benefits from Islamic Perspective - Babagana, Muhammad; Tukur, Bello (جامعة الوادي - University of Eloued, 2022)
Abstract : Marriage to more than one wife (Polygamy) is a practice as old as the history of man, and is allowed in Islamic Shariah law. This article aims to posit some benefits of polygamy to human in contemporary human race and detect some mis-understanding of western countries on polygamous nature of Islamic marriage and the failure they encounter in introducing new form of marriage based on their innovation (Same-sex relation). Finally, the research finds out that based on the establishment of new form of so called same-sex relation and transformed it into marital relationship have gotten contemporary human race into contracting diseases. The research also recommends that it is only through proper scholarly teaching of principle of marriage (polygamy) that problem of widow women and right of women can be protected.
المفهوم الغربي لتعدد الزوجات: دراسة لمفهوم التععد في المنظور الإسلامي
مقال
Keywords: Misconception; Western; Polygamy; Islam; Assessment; Benefit.; مفهوم خاطئ، الغرب، تعدد الزوجات، دين الإسلام، تقييم، المنفعة